Mammalian Target of Rapamycin: Is It Relevant to COPD Pathogenesis or Treatment?. (2nd January 2019) - Pasini, Evasio; Flati, Vincenzo; Comini, Laura; Olivares, Adriana; Bertella, Enrica; Corsetti, Giovanni; Vitacca, Michele
Abstract: The mammalian target of rapamycin (mTOR) signalling pathway regulates fundamental metabolic processes such as inflammation, autophagy and apoptosis, all of which influence cell fate. Recent experimental data suggest that mTOR signalling is involved in many diseases, including lung diseases, but with contrasting data. Overexpression of mTOR and its signalling proteins have been linked to lung cell senescence and development of emphysema, pulmonary hypertension and inflammation. On the other hand, mTOR inhibitors, as rapamycin and/or its derivatives, restore corticosteroid sensitivity in peripheral blood mononuclear cells from chronic obstructive pulmonary disease (COPD) patients, and overexpression of mTOR suppresses cigarette smoke-induced inflammation and emphysema, suggesting that induction of mTOR expression/activity might be useful to treat COPD. This apparent discrepancy is due to complex and heterogenic enzymatic pathway of mTOR. Translation of pre-clinical positive data on the use of mTOR inhibitors to COPD therapy needs a more in-depth knowledge of mTOR signalling.